Occurrence of the orange wheat blossom midge [Diptera :Cecidomyiidae] in Quebec and its incidence on wheat grain microflora / Présence de la cécidomyie orangée du blé [Diptera :Cecidomyiidae] au Québec et son incidence sur la microflore des grains de blé - Mongrain, D.; Couture, L.; Dubuc, J.-P.; Comeau, A. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1997)
Samples of wheat spikes (Triticum aestivum) were collected in the summer of 1995 from different crop districts in Quebec and the occurrence of orange wheat blossom midge (Sitodiplosis mosellana) and seed microflora were determined. Estimated yield loss caused by wheat midge larvae averaged 6.3%. The percentage of infested spikes was significantly correlated with total seed contamination by fungi and bacteria (r = 0.79). The specific occurrence of Fusarium graminearum in grains was also significantly correlated with number of larvae per spike (r = 0.67) or per spikelet (r = 0.67). Consequently, the wheat midge might play a role in dissemination of F. graminearum.